2021
DOI: 10.3389/fphys.2021.661959
|View full text |Cite
|
Sign up to set email alerts
|

The First Female Dry Immersion (NAIAD-2020): Design and Specifics of a 3-Day Study

Abstract: This article describes procedures and some results of the first study of females undergoing 3-day Dry Immersion. The experiment “NAIAD-2020” was carried out at the Institute of Biomedical Problems (Moscow, Russia) with the participation of six healthy women volunteers (age 30.17 ± 5.5 years, height 1.66 ± 0.1 m, weight 62.05 ± 8.4 kg, BMI 22.39 ± 2.2 kg/m2) with a natural menstrual cycle. During the study, a standard protocol was used, the same as for men, with a minimum period of time spent outside the immers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 40 publications
(53 reference statements)
1
11
0
Order By: Relevance
“…The study was conducted at the DI facility of the Institute of Biomedical Problems, Russian Academy of Science (Tomilovskaya et al, 2019(Tomilovskaya et al, , 2021. For 3 days, participants lay in the immersion bath without any physical activities and with moderate movement restriction; among other factors, lower limb activation was limited.…”
Section: Experimental Designmentioning
confidence: 99%
“…The study was conducted at the DI facility of the Institute of Biomedical Problems, Russian Academy of Science (Tomilovskaya et al, 2019(Tomilovskaya et al, , 2021. For 3 days, participants lay in the immersion bath without any physical activities and with moderate movement restriction; among other factors, lower limb activation was limited.…”
Section: Experimental Designmentioning
confidence: 99%
“…However, similar to the bed-rest model, studies during “dry” immersion are most often aimed at the musculoskeletal, nervous, and cardiovascular systems [ 15 , 16 , 17 , 18 ]. Moreover, the first “dry” immersion study with women as the subjects that lasted 3 days was conducted in 2020 [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is indicated by the results of the speech acoustic analysis and self-assessment questionnaires, in which the subjects noted an increase in anxiety and depression, and a decrease in activity. This was compared with the data obtained in the same experiment regarding the attitude of the subjects to their physical discomfort (such as general discomfort, back pain and abdominal pain) also peaking at the 1st day and decreasing by the 2nd day evening (Tomilovskaya et al, 2021). Previously, in studies with participation of astronauts (58% of whom were female) it was shown that approximately half of all astronauts report back pain during the early stages of spaceflight: back pain was most often reported on the first and 2nd days of space flight (Kerstman et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…From September 7 to November 30, 2020, the IBMP RAS conducted the world's first "dry" immersion experiment with the participation of female volunteers («NAIAD-2020») (Tomilovskaya et al, 2021).…”
Section: Design Of the Studymentioning
confidence: 99%